Co-Overexpression of OsNAR2.1 and OsNRT2.3a Increased Agronomic Nitrogen Use Efficiency in Transgenic Rice Plants - Chen, Jingguang; Liu, Xiaoqin; Liu, Shuhua; Fan, Xiaoru; Zhao, Limei; Song, Miaoquan; Fan, Xiaorong; Xu, Guohua (Frontiers in Plant Science, 2020)
The NO3- transporter plays an important role in rice nitrogen acquisition and nitrogen-use efficiency. Our previous studies have shown that the high affinity systems for nitrate uptake in rice is mediated by a two-component NRT2/NAR2 transport system. In this study, transgenic plants were successfully developed by overexpression of OsNAR2.1 alone, OsNRT2.3a alone and co-overexpression of OsNAR2.1 and OsNRT2.3a. In our field experiments, transgenic lines expressing p35S:OsNAR2.1 or p35S:OsNAR2.1-p35S:OsNRT2.3a constructs exhibited increased grain yields of approximately 14.1% and 24.6% compared with wild-type (cv. Wuyunjing 7, WT) plants, and the agricultural nitrogen use efficiency increased by 15.8% and 28.6%, respectively. Compared with WT, the 15N influx in roots of p35S:OsNAR2.1 and p35S: OsNAR2.1-p35S:OsNRT2.3a lines increased 18.9% - 27.8% in response to 0.2 mM, 2.5 mM 15NO3– and 1.25 mM 15NH415NO3, while there was no significant difference between p35S:OsNAR2.1 and p35S:OsNAR2.1-p35S:OsNRT2.3a lines; only the 15N distribution ratio of shoot to root for p35S:OsNAR2.1-p35S:OsNRT2.3a lines increased significantly. However, there were no significant differences in nitrogen use efficiency, 15N influx in roots and the yield between the p35S:NRT2.3a transgenic lines and WT. This study indicated that co-overexpression of OsNAR2.1 and OsNRT2.3a could increase rice yield and nitrogen use efficiency.